ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KETEPATAN WAKTU CORPORATE INTERNET REPORTING PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Widaryanti .; Eman Sukanto (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
This research examine which corporate governance mechanism can effect Timeline of Corporate Internet Reporting by listed companies on the Indonesian Stock Exchange. Independent variables in this study are firm characteristics (firm size, type of bussiness, profitability, leverage, liquidity, issuance of stock) and corporate governance variables (public ownership structure, proportion of supervisory board and supervisory board size) to investigate the influence on the timeliness of CIR. Population sample in this study was taken from Indonesian companies listed in 2012 at Indonesian Stock Exchange. Hypotesis analysis using Multiple regression. Based on the result of analysis showed that all variables simultaniously influence the timeliness of CIR. Only firm size that influence the timeliness of CIR.